Odpowiedzi

Najlepsza Odpowiedź!
2010-04-06T14:10:57+02:00
A) 12x-x-8x=8-3-4
3x=1 :3
x=1/3
b) x+2/-1=1-x/3 *3
3x + 6 :(-3)=3 -x +2,+x
4x=5 :4
x=4/5
c) 3z-2/8-2(4z-1)/12=
3z - 1/4 - (4z -1)/6 = *6
18z - 3/2 - 4z -1=
14z -2 1/2


Pozdrawiam;)
2010-04-06T14:16:57+02:00
A) nastepuje red. wyr. podobnych
3x=1 /:3
x=1/3
b)
x-2=1-x/3 /*3
x-2*3=1-x/3*3
x-6=1-x /+7
x=8-x /+x
2x=8 /2
x=4

c)
3z-2/8-2(4z-1)/12 /*8
3z-8-2/8*8-2*8(4z-1)/12*8
24z-2-16(4z-1)/3
24z-18(4z-1)/3
24z-6(4z-1)
24z-24z+6
0+6=6

coś w tym stylu ;] pozdro